Evaluation of deep-water environmental conditions during the latest Maastrichtian-early Danian: Insights from the western south atlantic ocean. (December 2021) - Krahl, Guilherme; Kochhann, Karlos G.D.; Fauth, Gerson; Sial, Alcides N.; Drude de Lacerda, Luiz
Abstract: The Cretaceous-Paleogene (K-Pg) boundary extinction event affected planktic foraminiferal assemblages worldwide in a dramatic way, but deep sea benthic foraminiferal assemblages were not significantly impacted. However, possible impacts of massive early Danian volcanic eruptions, such as those related to the Deccan Traps, on benthic foraminiferal assemblages are not yet explored. Here we present geochemical and benthic foraminiferal data across the K-Pg boundary and within the earliest Danian interval at Deep Sea Drilling Project (DSDP) Site 356, located on the São Paulo Plateau, western South Atlantic Ocean. Maastrichtian to Danian benthic foraminiferal assemblages are well-preserved and suggest deposition at middle to lower bathyal paleodepths, under an oligotrophic regime with well-oxygenated bottom water conditions. As expected, the K-Pg boundary event did not significantly affect benthic foraminiferal assemblages at Site 356. However, during the early Danian, benthic foraminiferal species richness, heterogeneity, diversity and equitability presented overall opposite trends in relation to the Hg/TOC and Hg/CaCO3 ratios, as well as Hg concentrations, which we consider proxies for intensity of volcanic activity. Our results suggest a possible response of Danian middle to lower bathyal benthic foraminiferal assemblages at Site 356 to changes in bottom water condition possibly associated with massive volcanism eruptions. Highlights: Geochemical characterization Mercury and Hg/TOC and Hg/CaCO3 ratio in deep-marine at Site 356 (São Paulo Plateau). Benthic foraminiferal assemblages suggest an oligotrophic regime with well-oxygenated bottom water conditions. Changes in benthic foraminiferal assemblages in bottom water condition possibly associated with massive volcanism eruptions.